URGENSI RESILIENSI DAN KOMPETENSI PROFESIONAL GURU DALAM MENGHADAPI TRANSFORMASI PEMBELAJARAN ERA DIGITAL DI SD ISLAM AL-AZHAR 6 JAKAPERMAI - Maisie_Maisie Zabrina Kusnaedi; Yohamintin_ Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Rapid technological developments require elementary school teachers to possess strong resilience and professional competence in facing the transformation of digital- era learning. This study aims to describe the urgency of improving the capabilities of teachers at Al-Azhar 6 Islamic Elementary School in Jakapermai in integrating technology into the learning process effectively and adaptively. A qualitative method with a case study approach was used to gather data through observation, interviews, and documentation studies. The results show that teachers at this school are highly motivated and have good adaptability to technological developments, supported by ongoing training, digital facilities such as tablets and smartboards, and full support from the school. Teachers not only act as instructors but also as facilitators who encourage active student participation and creative use of technology. Collaboration between teachers and regular evaluation are key strategies in overcoming the challenges of digital learning.